Natural antifibrosis potential of anthocyanin in Ipomoea batatas against Transforming Growth Factor beta Type II receptor by in silico ADMET and molecular docking study - Evi Lusiana; Ernawati Sinaga; Zen Hafy; Debby Handayati Harahap; Ramzi Amin; Irsan Saleh (Results in Chemistry)
Purple sweet potato (Ipomoea batatas) are known to have bioactive anthocyanin compounds with numerous human therapeutic benefits. Anthocyanins derived from I. batatas can suppress the action of Transforming Growth Factor beta Type II Receptor (TGFβRII) to prevent fibrosis progression. This study aims to examine the molecular features and bioactivity of anthocyanins in I. batatas and determine the interaction of six anthocyanins in I. batatas against TGFβRII through in silico studies. The TGFβRII protein was retrieved from the Protein Data Bank (PDB) database, while the I. batatas anthocyanin was acquired from the PubChem database. Proteins and ligands were docked utilizing the PyRx 0.8 and visualized by Discovery Studio 4.1 software. The in silico study results indicated peonidin-3-glucoside, pelargonidin-3-glucoside, cyanidin 3-o-galactoside, delphinidin 3-glucoside, peonidin 3-galactoside and, cyanidin 3-glucoside were revealed to be efficacious against TGFβRII. Analysis of protein–ligand interactions demonstrates that anthocyanins bind to amino acid residues in the target protein’s active site, and these anthocyanins have higher binding energy than the reference drug. I. batatas, one of the traditional medicinal plants containing anthocyanins, has the potential to generate effective therapeutic approaches for the treatment of fibrosis. Additional in-vitro and in-vivo research is highly recommended to comprehend the antifibrosis mechanism adequately.